Modification of Wheat, Sago and Tapioca Starches by Irradiation and its Effect on the Physical Properties of Fish Crackers (Keropok) - Mohd Adzahan, Noranizan (2002)
The effect of starch irradiation on the properties of fish crackers in relation to microstructure of starch in 'keropok' was investigated. Wheat, tapioca and sago starch were used. Linear expansion of 'keropok' was best when the swelling of granules, leaching of amylose and amylopectin were high. Irradiation has been investigated as a means of degrading the starch polymers, which leads to an increase in the amount of soluble materials leached. Microwave, electron beam and gamma ray irradiation were used to degrade the starch polymers. The Brabender Viscograph, Texture Analyser (TAXT2-i), Falling Ball Viscometer and Haake Rheometer were used to determine the rheological properties of the starch pastes and gels. Results showed that irradiation caused an increase in leaching, a concomitant drastic reduction in swelling volumes of starch granules, and rate of gelation. It also showed that the strength of starch gels, viscosity, viscoelasticity and intrinsic viscosity decreased as the levels of irradiation was increased, indicating a decrease in the molecular weight of starch polymers. These changes were due to the cleavage of the amylose and amylopectin fractions by radiation energy. Fish crackers made from irradiated wheat starches expanded significantly better than the native starch and were cnspler. However, after a certain level of irradiation, the expansion decreased although the values remained higher than the expansion values for 'keropok' from native starch. The expansion of some of these wheat and sago starches improved greatly as the values exceeded the acceptable level i.e., 77% expansion. 'Keropok' from microwave irradiated tapioca starch expanded significantly better than its native starch. On the other hand, electron beam and gamma irradiated tapioca starches seemed to produce 'keropok' with poor expansion properties and worse than the native starch. Good expansion was found in 'keropok' made from starches with high amounts of leaching and high molecular weight. Irradiated starch fish crackers were found to fracture at lower energy and had better crispiness properties despite that some crackers did not expand well. As a conclusion, irradiation of starch can improve the expansion and crispiness of fish crackers as it increases the leaching of amylose and amylopectin from the starch granules. The amylose and amylopectin can then be involved in the formation of starch-fish network, which allows the entrapment of water and will aid expansion during frying. The presence of higher molecular weight amylose and amylopectin will further contribute to better fonnation of this network. The ratio of amylose and amylopectin in the leachate would play a role in expansion, where higher amounts of amylopectin would give a better expanded fish crackers. High swelling ability and protein contents in starch are also contributing factors to expansion.